Integrasi Pendekatan Sistem, Multiple Intelligences, dan Nilai-nilai Islam dalam Proses dan Hasil Belajar - Nur Manna; Nurfarida Deliani; Juliana Batubara (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to develop a conceptual synthesis of the factors influencing the learning process and learning outcomes by integrating the educational systems approach, the Multiple Intelligences theory, and Islamic values. A library research method with content analysis was employed to examine relevant national and international books and scholarly publications. The findings indicate that learning outcomes are shaped by the interaction among raw input, instrumental input, environmental input, the learning process, output, and outcome. The Multiple Intelligences theory broadens the understanding of students' diverse potentials, while Islamic values provide a spiritual and moral foundation for meaningful learning. This study proposes a holistic learning model that integrates the systems approach, multiple intelligences, and Islamic values as a foundation for learning in the digital era. The findings emphasize that optimizing learning outcomes requires strengthening not only academic achievement but also students' character, morality, and spirituality in a balanced manner.